2023
DOI: 10.1038/s41467-023-37009-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh loading dry-process for solvent-free lithium-ion battery electrode fabrication

Abstract: The current lithium-ion battery (LIB) electrode fabrication process relies heavily on the wet coating process, which uses the environmentally harmful and toxic N-methyl-2-pyrrolidone (NMP) solvent. In addition to being unsustainable, the use of this expensive organic solvent substantially increases the cost of battery production, as it needs to be dried and recycled throughout the manufacturing process. Herein, we report an industrially viable and sustainable dry press-coating process that uses the combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…It is interesting to note that some very recent studies have indicated that the property of the CEI layers formed on DPEs and conventional electrodes is different, and DPEs indeed exhibit better electrochemical performance than conventional electrodes do. 16,18,60 In view of the aforementioned analyses, the impact of the electrolytes on the high-loading PTFE-based DPEs can be ascribed to the following two aspects. (1) Electrolytes with different properties play a significant role in the electrochemical performance, especially ionic conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that some very recent studies have indicated that the property of the CEI layers formed on DPEs and conventional electrodes is different, and DPEs indeed exhibit better electrochemical performance than conventional electrodes do. 16,18,60 In view of the aforementioned analyses, the impact of the electrolytes on the high-loading PTFE-based DPEs can be ascribed to the following two aspects. (1) Electrolytes with different properties play a significant role in the electrochemical performance, especially ionic conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, the HRXPS analyses of the transition metal species confirm that the LiClO 4 -based electrolyte leads to a thinner CEI layer than the LiPF 6 -based electrolyte does. It is interesting to note that some very recent studies have indicated that the property of the CEI layers formed on DPEs and conventional electrodes is different, and DPEs indeed exhibit better electrochemical performance than conventional electrodes do. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Lithium ion batteries (LIBs), which have the advantages of high capacity and power density, are considered to be a key component that determines the driving performance of overall vehicle. 1–4 Among the commercialized LIBs, lithium iron phosphate (LiFePO 4 , LFP) batteries are widely used and represent more than 32% of the overall LIB market share owing to their superior safety, earth-abundant iron sources, and relatively low production costs. Although LFP is regarded as an ecofriendly material, its improper disposal will create serious environmental crises.…”
Section: Introductionmentioning
confidence: 99%
“…This modification reduces their tendency to aggregate 32,33 while increasing their affinity for active materials, leading to improved electrochemical reaction kinetics of the given dryprocessed LIB electrode even with low amounts of conductive agents. 34 The use of liquid-phase strong acidic oxidizers, such as mixed acid, 29,30 can effectively introduce functional groups to the CNT surfaces; however, they can also severely damage the sp 2 system of nanotubes, resulting in decreased electrical conductivity, which calls for optimization based on trials and errors and extra drying processes.…”
mentioning
confidence: 99%
“…However, their tendency to aggregate limits dispersion and active material contact when mixed without solvent, especially at high electrode loading levels. Surface functionalization of CNTs with various strong liquid-phase oxidants can introduce oxygen-based functional groups, such as carboxylic acid, hydroxyl, and carbonyl groups, to the surface of CNTs. This modification reduces their tendency to aggregate , while increasing their affinity for active materials, leading to improved electrochemical reaction kinetics of the given dry-processed LIB electrode even with low amounts of conductive agents . The use of liquid-phase strong acidic oxidizers, such as mixed acid, , can effectively introduce functional groups to the CNT surfaces; however, they can also severely damage the sp 2 system of nanotubes, resulting in decreased electrical conductivity, which calls for optimization based on trials and errors and extra drying processes.…”
mentioning
confidence: 99%